Some notes on the life of a book - Tiago Mata (Duke University, Center for the History of Political Economy (CHOPE), 2021)
In 2022, Cambridge University Press is publishing a 50th anniversary edition of Geoff Harcourt's Some Cambridge Controversies in the Theory of Capital. There will be two afterwords, preceded with this introduction: You have before you CUP's 50th anniversary edition of Geoff Harcourt's Some Cambridge Controversies in the Theory of Capital. The book is worthy of republication, and if the reader is not convinced by the text alone, these afterwords offer an explanation. Tiago Mata's essay is a study of the book's global career, tracing its reach in terms of geography and in terms of readerships. Avi J. Cohen's essay addresses the role of the man in shaping how we think about economics and its history, and in influencing new generations of economists.
Keywords: A11; B22; B50; 330; book history; capital controversies; economics as print; circulation of ideas